Antibody‐Mimetic Peptoid Nanosheet for Label‐Free Serum‐Based Diagnosis of Alzheimer's Disease. Issue 30 (12th June 2017) - Zhu, Ling; Zhao, Zijian; Cheng, Peng; He, Zhaohui; Cheng, Zhiqiang; Peng, Jiaxi; Wang, Huayi; Wang, Chen; Yang, Yanlian; Hu, Zhiyuan
Abstract : Alzheimer's disease (AD) is the most common form of dementia characterized by progressive cognitive decline. Current diagnosis of AD is based on symptoms, neuropsychological tests, and neuroimaging, and is usually evident years after the pathological process. Early assessment at the preclinical or prodromal stage is in a great demand since treatment after the onset can hardly stop or reverse the disease progress. However, early diagnosis of AD is challenging due to the lack of reliable noninvasive approaches. Here, an antibody‐mimetic self‐assembling peptoid nanosheet containing surface‐exposed Aβ42‐recognizing loops is constructed, and a label‐free sensor for the detection of AD serum is developed. The loop‐displaying peptoid nanosheet is demonstrated to have high affinity to serum Aβ42, and to be able to identify AD sera with high sensitivity. The dense distribution of molecular recognition loops on the robust peptoid nanosheet scaffold not only mimics the architecture of antibodies, but also reduces the nonspecific binding in detecting multicomponent samples. This antibody‐mimetic 2D material holds great potential toward the blood‐based diagnosis of AD, and meanwhile provides novel insights into the antibody alternative engineering and the universal application in biological and chemical sensors. Abstract : An antibody‐mimetic self‐assembling peptoid nanosheet that is functionalized with surface‐exposed Aβ42‐recognizing loops is developed for label‐free high‐sensitive detection of Alzheimer's disease (AD) serum. This antibody‐mimetic 2D material holds great potential toward the blood‐based diagnosis of AD, and provides insights into the antibody alternative engineering and the universal application in biological and chemical sensors.